Resolving Village Head Election Disputes: Legal Pathways in State Administrative Courts - Firdaus Arifin; Ihsanul Maarif; A, Rika Kurniasari; M. Nabiel Fadlilah (Nurani, 2024)
This research examines the legal certainty surrounding the time limits for resolving disputes over the results of Village Head elections through the State Administrative Court. The absence of clear regulations on the deadlines and mechanisms for addressing these disputes has led to various issues, including legal uncertainty, inequality in treatment, and perceptions of injustice among stakeholders. To address these concerns, this study adopts a normative juridical approach, relying on an extensive literature review of legal principles, norms, doctrines, and regulations. The findings reveal that disputes regarding Village Head election results must be submitted within three days of receiving notification or a formal decision from the Regent or Mayor. The State Administrative Court (PTUN) is then required to issue a ruling within 14 working days from the date the case is officially recorded in the case register. Moreover, the court’s decisions are final and binding, meaning no further legal actions or appeals are permitted. This process ensures that disputes arising from Village Head elections are resolved definitively and conclusively, providing a legally certain outcome while upholding the principles of justice and fairness in election-related matters.